A Data‐Driven Possibilistic Approach to the Identification of Uncertain Stability Lobe Diagrams. Issue 1 (17th December 2018) - Hose, Dominik; Hamann, Dominik; Hanss, Michael; Eberhard, Peter
Abstract: In this contribution, an alternative approach to classical regression analysis is explored which allows the identification of uncertain stability lobe diagrams for machining processes via a multi‐fidelity modeling approach.